Why flow-completion time is the right metric for congestion control. - Dukkipati, Nandita (Computer communication review.)
Users typically want their flows to complete as quickly as possible. This makes Flow Completion Time (FCT) an im portant - arguably the most important - performance metric for the user. Yet research on congestion control focuses almost entirely on maximizing link throughput, utilization and fairness, which matter more to the operator than the user. In this paper we show that with typical Internet flow sizes, existing (TCP Reno) and newly proposed (XCP) congestion control algorithms make flows last much longer than necessary - often by one or two orders of magnitude. In contrast, we show how a new and practical algorithm - RCP (Rate Control Protocol) - enables flows to complete close to the minimum possible